The Effect of Counseling Training for Health Cadres on the Skills of Providing Information on Tuberculosis Treatment at Dempar Health Center, Nyuatan District, West Kutai Regency - Adriana Suviani; Joko Sapto Pramono; Mustaming (PT FORMOSA CENDEKIA GLOBAL, 2023)
The success rate of tuberculosis treatment in East Kalimantan Province is still below the national target. This study aims to analyze the effect of counseling training on the skills of cadres in providing information on tuberculosis treatment at the Dempar Health Center. The research design was a quasi experiment without a control group. The training intervention was tuberculosis treatment counseling, cadre skills were measured before and after the intervention. Samples were taken as a total population of 40 respondents. Data analysis used the Wilcoxon test to determine the difference in the average pre and post intervention scores. The results showed that there was an increase in the ability of cadres to provide TB treatment counseling after being given training, p-value = 0.000 (< α = 0.05). The author concludes the need for counseling training for cadres to be able to provide information on tuberculosis treatment.